2007
DOI: 10.1126/science.1146824
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Inositol Pyrophosphates for Full Exocytotic Capacity in Pancreatic β Cells

Abstract: Inositol pyrophosphates are recognized components of cellular processes that regulate vesicle trafficking, telomere length, and apoptosis. We observed that pancreatic beta cells maintain high basal concentrations of the pyrophosphate diphosphoinositol pentakisphosphate (InsP7 or IP7). Inositol hexakisphosphate kinases (IP6Ks) that can generate IP7 were overexpressed. This overexpression stimulated exocytosis of insulin-containing granules from the readily releasable pool. Exogenously applied IP7 dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
211
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(216 citation statements)
references
References 23 publications
5
211
0
Order By: Relevance
“…3c). This data correlates with the observations of Illies et al (25) that RNA silencing of IP6K1 in pancreatic beta cells inhibits exocytosis of insulin-containing granules from the readily releasable pool. There- …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…3c). This data correlates with the observations of Illies et al (25) that RNA silencing of IP6K1 in pancreatic beta cells inhibits exocytosis of insulin-containing granules from the readily releasable pool. There- …”
Section: Resultssupporting
confidence: 81%
“…A putative disruption of the IP6K1 gene has been described in a family with type 2 diabetes (24). Illies et al recently showed that selective depletion of IP6K1 by RNA interference in pancreatic beta cells impairs insulin secretion (25). To elucidate the physiologic role of IP6K1, we created mice with a targeted deletion of the exon encoding the C-terminal catalytic domain.…”
mentioning
confidence: 99%
“…Recent studies indicated that the size of the primed vesicle pool in insulin-secreting pancreatic ␤ cells was dependent on the level of diphosphoinositol pentakisphosphate (48), which non-enzymatically pyrophosphorylates proteins on phosphoSer residues within CK2 consensus sites (49). Whether CAPS is further activated by diphosphoinositol pentakisphosphatemediated pyrophosphorylation to enhance vesicle priming will require further study.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, InsP7 has been implicated in several cellular functions, including vesicular trafficking and exocytosis (26,27), apoptosis (28)(29)(30)(31), insulin disposition (32), insulin sensitivity, and weight gain (33). We recently showed that InsP7 also represents a mechanism for controlling optimal PtdIns(3,4,5)P3/Akt pathway activation in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Total and phosphorylated Akt were detected by Western blot using anti-Akt and anti-phospho-Akt (Ser473) antibodies, respectively. Relative amounts of phosphorylated Akt were quantified using NIH Image software as described (26). All samples were normalized to the amount of total Akt.…”
Section: Effects Of Cse and Nicotine On Neutrophil Spontaneous Death mentioning
confidence: 99%